TYPES OF MOTOR AND MENTAL TRAINING AND THEIR IMPACT ON IMPROVING SKIERS’ SKILLS – A REVIEW ARTICLE - Karol Marcyś; Wojciech Ługowski; Julia Samek; Jakub Komorowski-Roszkiewicz; Weronika Matwiejuk; Karolina Bartosiewicz; Iga Kwiecień; Kamil Dziekoński (International Journal of Innovative Technologies in Social Science, 2025)
This review article consolidates current evidence on the role of motor and mental training in enhancing skiing performance across alpine, cross-country, and ski jumping disciplines. Analysis of 21 original research studies revealed that simulation-based and imitative motor training significantly improve interlimb coordination, postural control, and technical precision—especially during ski turns and take-off phases. In ski jumping, biomechanical refinement and repetition-based imitation enhance energy transfer and movement stability. Mental and perceptual training components—including psychological resilience, low anxiety, and predictive cognitive strategies—are associated with improved skill acquisition, faster reaction times, and more consistent performance under competitive stress. Balance training, particularly when sport-specific, was shown to predict technical proficiency and reduce fall-related injuries by improving neuromuscular control. Injury prevention strategies focused on understanding key trauma mechanisms such as ACL-related slip-catch and improper landings, with emphasis placed on correcting technique and adapting equipment to skill level. Furthermore, strength and endurance training support fatigue resistance and biomechanical control, with special relevance to upper-body output in cross-country skiing and load management in alpine disciplines. Youth-specific training strategies should be guided by biological maturity rather than chronological age to support safe and effective athletic development. Collectively, the findings support a multidisciplinary, individualized, and periodized approach to skier development. This synthesis provides evidence-based guidance for training program design and identifies areas for future longitudinal research.